Bismuth-modified hydroxyapatite carbon electrode for heavy metal detection in biomatrices - Ajab, H. (Trans Tech Publications Ltd, 2014)
Micro-analytical based sensors with complex biomatrices such as blood, urine, or saliva are of increasing interest in health-care sector because of their sensitivity, selectively and simplicity. A modified carbon electrode with hydroxyapatite (HAp) and Bismuth (II) was developed to detect Pb2+ concentration in blood sera from healthy persons. Square wave anodic stripping voltammetry was used for the detection of Pb2+ by the interacting capability of the Bi film and HAp on the electrode surface with the optimised parameters of deposition time 240sec, deposition potential â1.0 V in 0.1M acetate buffer followed by square wave potential scan from -1.0 V to -0.2V. Bi film deposited HAp-CME showed attractive electrochemical characteristics with high sensitivity for Pb2+. Clear current peaks for different Pb2+ concentrations were observed around -0.55V, with favourable signal-to-background ratio, and comparatively free from oxygen interferences. Â© 2014 Trans Tech Publications, Switzerland.